2023
DOI: 10.3390/e25040667
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Recent Earthquake Swarms in Greece in Terms of Non-Extensive Statistical Physics

Abstract: Greece exhibits the highest seismic activity in Europe, manifested in intense seismicity with large magnitude events and frequent earthquake swarms. In the present work, we analyzed the spatiotemporal properties of recent earthquake swarms that occurred in the broader area of Greece using the Non-Extensive Statistical Physics (NESP) framework, which appears suitable for studying complex systems. The behavior of complex systems, where multifractality and strong correlations among the elements of the system exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
(231 reference statements)
0
3
0
Order By: Relevance
“…Such weak interaction systems do not have a Boltzmann distribution, but rather a powerlaw distribution with heavy tails, enhanced by (multi) fractal geometry, long-range interactions, and intermittence or large fluctuations between various possible states. These systems correspond precisely to seismic phenomena (Sardeli et al, 2023;Sigalotti et al, 2023;Vallianatos et al, 2016). For such systems, Tsallis (1988) established nonextensive statistical mechanics and generalized Boltzmann-Gibbs statistical mechanics.…”
Section: Deep Underground Science and Engineeringmentioning
confidence: 98%
“…Such weak interaction systems do not have a Boltzmann distribution, but rather a powerlaw distribution with heavy tails, enhanced by (multi) fractal geometry, long-range interactions, and intermittence or large fluctuations between various possible states. These systems correspond precisely to seismic phenomena (Sardeli et al, 2023;Sigalotti et al, 2023;Vallianatos et al, 2016). For such systems, Tsallis (1988) established nonextensive statistical mechanics and generalized Boltzmann-Gibbs statistical mechanics.…”
Section: Deep Underground Science and Engineeringmentioning
confidence: 98%
“…These methods have been applied to a wide range of fields, such as high energy scattering processes [4,5,6], Ising systems [7], cosmic ray physics [8,9], plasma physics [10,11], ultracold gases [12], non-Gaussian diffusion processes in small complex systems [13,14], power grid frequency [15], bacterial DNA [16], financial time series [17,18] and traffic delays [19,20]. Recent years have also witnessed an increase in its application in environmental sciences, including wind statistics [21], air pollution statistics [22,23], rainfall statistics [24], sea surface currents [25], earthquake swarms [26,27] and water quality time series [28]. The dynamics of river water quality indicators, which involve a complex interplay of physical, chemical, and biological processes, can be viewed as a superposition of various dynamics across different time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Collective parameters can be extremely useful for characterizing the clustering properties of seismicity [ 19 , 20 , 21 , 22 ]; moreover, more recently, it has been suggested that they can be related to the behavior of seismogenetic sources at a regional scale [ 23 ]. Therefore, they may be of interest to infer the seismogenic potential of still poorly investigated areas.…”
Section: Introductionmentioning
confidence: 99%